2020
DOI: 10.6018/analesdoc.440101
|View full text |Cite
|
Sign up to set email alerts
|

Hábitos de publicación de la élite científica de España

Abstract: El objetivo de este estudio consiste en analizar los patrones de autoría y hábitos de publicación de los investigadores de España más productivos y/o citados. Método: Se han seleccionado los investigadores españoles o que trabajan en instituciones españolas, con mayor índice H y número de citas recibidas en Google Scholar (GS) a partir del Webometrics Ranking of World Universities. Los datos de las publicaciones se han obtenido de la colección principal de Web of Science (WOS). Resultados y conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…This phenomenon has become constant in some parts of the world. For example, in Spain, many institutions have benefited from hyperprolific authors, where they improve their indexes in the webometric ranges, (17) in a study where they analyzed the authorship patterns of researchers, aiming to identify the productivity and impact of the country's scientific elite, where they compared Google Scholar https://doi.org/10.56294/sctconf2023444 data with that of the Web of Science, the percentage in which authors sign with the first author, and the degree of highly productive authors (hyperprolific). In the study, they identified that the most adept authors of high productivity processes without impact and in almost always the same journals were from the Social Sciences and Humanities, but they warn that in the case of experimental physics, the excessive number of authors also has an aspect of super-billing scientific productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This phenomenon has become constant in some parts of the world. For example, in Spain, many institutions have benefited from hyperprolific authors, where they improve their indexes in the webometric ranges, (17) in a study where they analyzed the authorship patterns of researchers, aiming to identify the productivity and impact of the country's scientific elite, where they compared Google Scholar https://doi.org/10.56294/sctconf2023444 data with that of the Web of Science, the percentage in which authors sign with the first author, and the degree of highly productive authors (hyperprolific). In the study, they identified that the most adept authors of high productivity processes without impact and in almost always the same journals were from the Social Sciences and Humanities, but they warn that in the case of experimental physics, the excessive number of authors also has an aspect of super-billing scientific productivity.…”
Section: Literature Reviewmentioning
confidence: 99%